VALUE-BASED MANAGEMENT CAPITALISM VS SOCIALISM PROBLEMS IN THE ISLAMIC ECONOMIC: VALUE-BASED MANAGEMENT CAPITALISM VS SOCIALISM PROBLEMS IN THE ISLAMIC ECONOMIC - Joki Hartono Tri Nugroho; Regas Panji Pratomo; Indrian Sasmito Adi, Handaru (Airlangga Development Journal, 2024)
The problem with both economic systems, capitalism and socialism, is that they cannot achieve the desires and aspirations of the people as actors of economic policy. Both systems prioritize profit over satisfaction or people's rights. Departing from the various problems that exist in society, the author tries to examine this problem by organizing the two Islamic economic systems. The aim is to examine the problems faced by the economic systems of capitalism and socialism in dealing with economic problems and also to see how the Islamic economic system deals with economic problems. Desk research, or "book research," is the methodology used. This is a qualitative type of research, and the data presented is more subjective and literature-focused. Unlike capitalism, which grants ownership rights over the means of production to each person, socialism does not recognize individual ownership rights and instead grants ownership rights to the collective.   Keywords: Capitalism Value Based Management, Islamic Economics, Socialism based Management